Educational Supply Chain Management: A View on Professional Development Success in Malaysia - K. L., Lee; G., Nawanir; J. K., Cheng; Haitham M., Alzoubi; Muhammad, Alshurideh (Springer Science and Business Media Deutschland GmbH, 2023)
The industrial environment is unpredictably shifting. Technology advancements and pandemics force the corporate environment to evolve even faster in order to stay competitive and thrive. As a result, in today's fast-paced business environment, supply chain management has grown in popularity. The study's major goal is to apply the concept of industrial supply chain management to educational management. The empirical study will be conducted separately and do not cover in this paper. In dynamic and uncertain business operations, the educational model is more appropriate to switch from mass production delivery to industrial experiences in building individual talent excellence. This minimizes the educator's knowledge and experiences delivery gap to the learner in the educational supply chain. From the issues, This study identifies the education attributes and how it affects professional development success. This study further investigates the moderating effect of industrial experiences on the relationship between education attributes and professional development success. Besides, this study aims to propose an educational supply chain model (EduSCM) for 21st-century professional development success in Malaysia higher education to gain competitive advantages. To achieve the objectives, mixed methods research design is proposed. The qualitative data collection will be collected after the completion of quantitative data analysis. The data collected from the interview use to explain, interpret, understand, and triangulate the results of quantitative analysis to produce a potent conclusion. Lastly, this study will provide a unique conceptual diagram expected to aid researchers and practitioners to create a more comprehensive understanding of the linkages between learning competencies, industrial experiences, and professional development.